2020
DOI: 10.1371/journal.pone.0234729
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent effects of chronic intermittent voluntary alcohol consumption on attentional, not motivational, measures during probabilistic learning and reversal

Abstract: Background Forced alcohol (ethanol, EtOH) exposure has been shown to cause significant impairments on reversal learning, a widely-used assay of cognitive flexibility, specifically on fully-predictive, deterministic versions of this task. However, previous studies have not adequately considered voluntary EtOH consumption and sex effects on probabilistic reversal learning. The present study aimed to fill this gap in the literature. Methods Male and female Long-Evans rats underwent either 10 weeks of voluntary in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 81 publications
(120 reference statements)
7
23
2
Order By: Relevance
“…Finally, we found that differences in reward collection latencies depended on the richness of the environment (90% vs 70% reward). Notably, the only pronounced sex difference was in longer latencies to choose the better option during reversal learning (females taking longer than males), which is generally consistent with the pattern of effects of a recent study by our group (Aguirre et al, 2020). We elaborate on these findings below.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Finally, we found that differences in reward collection latencies depended on the richness of the environment (90% vs 70% reward). Notably, the only pronounced sex difference was in longer latencies to choose the better option during reversal learning (females taking longer than males), which is generally consistent with the pattern of effects of a recent study by our group (Aguirre et al, 2020). We elaborate on these findings below.…”
Section: Discussionsupporting
confidence: 85%
“…Further, we found that differences in reward collection latencies depended on the degree to which the environment was profitable (90% vs 70% reward). Finally, the only pronounced sex differences were uncovered for initiation latencies across both learning phases, and a greater number of initiation omissions during reversal learning, suggesting greater attentional demands in females relative to males, which replicate effects of a recent study by our group (Aguirre et al, 2020). We elaborate on these findings below.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In some rodent models, prior alcohol exposure has impaired both the initial discrimination and the later reversal [9][10][11][12], whereas other experimental conditions found the original discrimination unimpaired and found a selective deficit in reversal learning [9,[13][14][15][16][17][18]. However, many studies have instead found that prior alcohol exposure does not lead to a discrimination or a reversal learning impairment [19][20][21][22][23][24][25]. The prior literature on the long-term effects of alcohol exposure on reversal learning spans procedures from multiple laboratories, which differ in multiple experimental factors (e.g., type of reversal learning task, method and dose of alcohol exposure, age of alcohol exposure, alcohol-test interval), and does not fit a consistent pattern in which a single factor can explain all of the conflicting results.…”
Section: Introductionmentioning
confidence: 99%